Progressive multiple cranial neuropathies presenting as a delayed complication of radiotherapy in infancy. Issue 750 (April 1988) - Pall, H. S.; Nightingale, S.; Clough, C. G.; Spooner, D.
Abstract : A 38 year old woman who had undergone irradiation during infancy for a left facial cutaneous arteriovenous malformation sequentially developed complete palsies of the ipsilateral VII, V, XI, IX, X, XII and VI cranial nerves. Apart from optic and olfactory nerve damage there are few reports of radiotherapy causing cranial nerve injury. We link the unusually extensive and progressive neural damage and the prolonged latency to the patient's age at time of irradiation.